STRATEGI GURU DALAM MENGATASI PERILAKU MENYENDIRI PADA SISWA DI SDN 40 INPRES PAPPOTA - Uhwah Hasanah; Nurfadillah Aulia Arman; Asmirinda Resa; Evy Segarawati Ampry; Muh. Inayah A.M.; Munawir Anas (IKIP Siliwangi, 2026)
Solitary behavior in elementary school students is one of the problems in social-emotional development that can hinder children's ability to adapt both academically and socially. This condition is reflected in students’ tendencies to avoid interaction, withdraw from peers, show low participation in group activities, and display minimal social responses in the learning environment. This study aims to identify the factors causing withdrawal behavior and to describe teachers’ strategies in addressing it at SDN 40 Inpres Pappota.The research employs a descriptive qualitative method through observation, interviews, and documentation. The literature review indicates that solitary behavior is influenced by internal factors such as low self-confidence, social anxiety, and communication barriers, as well as external factors such as parenting styles, unsupportive social environments, and limited opportunities for interaction. Various studies show that effective teacher approaches include cooperative learning, strengthening positive teacher–student relationships, light counseling, social skills training, and collaborative games.This study is expected to serve as a consideration for teachers in designing appropriate interventions to help students develop their social skills, particularly at SDN 40 Inpres Pappota.